Level of information systems in Turkish public ports and direction of improvement. Issue 6 (3rd July 2008) - Keceli, Yavuz; Choi, Hyung Rim
In the recent decades, the competition between seaports has become severe due to several factors, such as globalisation, increasing amount of international trade, advent of ultra-large container vessels, technical developments in cargo handling and changing demands of the customers. International transport environment has changed into a 'hub-and-spoke' system, in which cargo is shipped to a major hub port by ultra-large container vessels and trans-shipped to smaller ports by feeder ships. For this reason, ports around the world have invested heavily in their infrastructure and operating systems. On the other hand, it is a fact that Turkish ports fell behind in this competition and operational inefficiencies are affecting Turkish economy severely. Therefore, the aim of this paper is to enlighten the improvement direction of information systems for Turkish major public ports, which are currently operated by Turkish State Railways (TCDD). For this purpose, the past and present condition of information systems were seized and compared to that of world's advanced ports. Then the characteristics of information systems that can solve the current problems were outlined. According to the results, the problems of information systems in Turkish ports are mainly based on administrative incapability, rather than technical or economical.